Of mice and wrens: the relation between abundance and geographic range size in British mammals and birds - Blackburn, T. M. (1997)
We examine the relation between population size and geographic range size for British breeding birds and mammals. As for most other assemblages studied, a strong positive interspecific correlation is found in both taxa. The relation is also recovered once the phylogenetic relatedness of species has been controlled for using an evolutionary comparative method. The slope of the relation is steeper for birds than for mammals, but this is due in large part to two species of mammals that have much higher population sizes than expected from their small geographic ranges. These outlying mammal species are the only ones in Britain to be found only on small offshore islands, and so may be exhibiting density compensation effects. With them excluded, the slope of the abundance–range size relation for mammals is not significantly different to that for birds. However, the elevation of the relation is higher for mammals than for birds, indicating that mammals are approximately 30 times more abundant than birds of equivalent geographic range size. An earlier study of these assemblages showed that, for a given body mass, bats had abundances more similar to birds than to non-volant mammals, suggesting that the difference in abundance between mammals and birds might be due to constraints of flight. Our analyses show that the abundance–range size relation for bats is not different for that from other mammals, and that the anomalously low abundance of bats for their body mass may result because they have smaller than expected geographic extents for their size. Other reasons why birds and mammals might have different elevations for the relation between population size and geographic range size are discussed, together with possible reasons for why the slopes of these relations might be similar.